Wireless Rechargeable Sensor Networks - Yu, Chang-Wu (Energies (Basel), 2021)
[...]energy saving and cost reduction is a significant factor in the development of future localization networks. Simulation tools based on high frequencies are used to characterize the channel propagation and to obtain the ray-tracing data. [...]their fingerprinting technique requires a costly initial learning phase for cell fingerprint generation. The third paper considers energy harvesting issues in WSNs. Since energy harvesting sensors can be the solution to enabling future applications, in [3], Zareei et al. analyzed the performance improvement and evaluation of energy harvesting sensors in various situations.